Anticancer pentamethinium salt is a potent photosensitizer inducing mitochondrial disintegration and apoptosis upon red light illumination - Krejcir, Radovan; Briza, Tomas; Sterba, Martin; Simoncik, Oliver; Muller, Petr; Coates, Philip J; Martasek, Pavel; Vojtesek, Borivoj; Zatloukalova, Pavlina (Journal of photochemistry and photobiology. B, Biology, 2020)
Despite progress in the development and application of novel therapeutic agents, cancer remains a major cause of death worldwide. Therefore, there is a need for new approaches to increase therapeutic options and efficiency. The metabolism of cancer cells differs from that of non-malignant cells and their mitochondria show altered activities that can be utilized as a target for drug development. Salt 1 is a low-molecular weight heterocyclic compound of the polymethine class that accumulates in the mitochondria of cancer cells and selectively disrupts their metabolism. Salt 1 leads to a non-apoptotic form of cell death in vitro that is associated with an autophagic cellular response and eventual metabolic collapse, and inhibits human tumor xenograft growth in vivo without apparent toxicity for normal cells. As a pentamethinium compound, salt 1 exhibits intrinsic fluorescence and is a candidate for photosensitization after excitation by appropriate wavelengths of light. Herein, we report that salt 1 is a potent photosensitizer, which generates a photodynamic effect and provides enhanced cytotoxicity compared to salt 1 without light exposure. Importantly, photosensitization is optimally induced by red light, which is used clinically for photosensitization and penetrates further into tissues than lower wavelengths. Cancer cells treated with non-cytotoxic doses of salt 1 and subsequently exposed to 630 nm light show severely damaged mitochondria, manifested by reduced mitochondrial membrane potential and disintegration of the mitochondrial tubular network. As a consequence, cancer cells lose their proliferative potential and die via apoptosis in the presence of light. These findings indicate that salt 1 is a promising photosensitizer with potential to be combined with 630 nm light to strengthen its efficacy in cancer therapy.
Keywords: Photochemotherapy; Mitochondria; Photosensitizer; mitochondrie; fotosenzibilizující látky; Salts; soli; fotochemoterapie; Cell Line, Tumor; Photosensitizing Agents; reaktivní formy kyslíku; Reactive Oxygen Species; Cancer therapy; Bis-Trimethylammonium Compounds; Polymethine compounds; lidé; Humans; bistrimethylamoniové sloučeniny; apoptóza; Photodynamic therapy; nádorové buněčné linie; Apoptosis; Cyanine dyes